Normatifitas Keterlibatan Perempuan dalam Proses Legislasi Nasional Perspektif Feminist Legal Theory - Siti Masruroh; Irham Bashori Hasba (Universitas Jember, 2022)
The inclusiveness of women's lives is not enough if it only about social life, but it must also be involved in every process of formulating state legislation through the legislature. To fulfill this, women must be actively connected in the electoral process in parliamentary seats held and women's representation, The role of woman in national legislation is a form of effort to make legal products that are inclusive of woman's lives. The role of women in national legislation is very important considering that every year there are considerable amount of women who nominate themselves as legislators. There are two research questions provided in this study; the first is how woman's political rights portrayed in national legislation according to Act No.7 of 2017. It aims to find out how woman's political rights portrayed in national legislation according to Act No.7 of 2017. This is the basic foundation of women's political rights which have been regulated in the law which includes a 30 percent quota of women in legislation. The second research question is, how the concept of women's political rights in national legislation according to Yusuf Al-Qardhawi. It aims; (1) to explain the concept of this contemporary scholars, Yusuf Al-Qardhawi, regarding to his opinion, (2) to compare the law in Indonesia with the concept of Yusuf Al-Qardhawi on his partiality towards the role of women as legislators. This research is a type of normative legal research or literature study. This research uses a combination of approaches, they are law approach and conceptual approach. The data source used is a secondary data source. The data analysis method used is by analyzing the application of hermeneutics or interpretation. The results of this study show that; First, Act No. 7 of 2017 on general elections, what needs to be underlined in this case is that the biggest challenge of achieving the results of the 2014 legislative election, there are improvements in the administrative sector of the General Election Commission (KPU), not only with sanctions given to the party in fulfilling the 30 percent quota but also emphasizing understanding towards women before nominating themselves as legislators with political education and understanding them the importance of the 30 percent quota. Secondly, The concept offered by contemporary scholar Yusuf Qardhawi regarding the representation of women in the realm of national legislation in Parliament is very moderate and follow the times. Keywords: Women’s Role , National Legislation , Act No.7 of 2017, Yusuf Al-Qardhawi's concept